2016
DOI: 10.1620/tjem.239.67
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Takayasu Arteritis Is Associated with the HLA-B52 Allele in Japanese Patients

Abstract: Takayasu arteritis (TA) is a type of vasculitis that affects the large elastic arteries, specifically the aorta and its main branches. It has been reported that TA occurred most frequently in Nagasaki Prefecture, the western area in Japan. We retrospectively collected the information of 34 patients with TA, diagnosed using the American College of Rheumatology 1990 criteria for the classification of TA, from the medical records of Nagasaki University Hospital from 2003 to 2015, and we investigated the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Various studies have shown the critical role of specific cytokine profiles and immunologic pathways in the promotion of vascular inflammation and disease activity in patients with TAK . Furthermore, genetic factors are known to play an important role in the pathophysiology of TAK . However, none of these potential causes underlying the differences in disease activity between children and adults with TAK have yet been evaluated in comparative studies.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown the critical role of specific cytokine profiles and immunologic pathways in the promotion of vascular inflammation and disease activity in patients with TAK . Furthermore, genetic factors are known to play an important role in the pathophysiology of TAK . However, none of these potential causes underlying the differences in disease activity between children and adults with TAK have yet been evaluated in comparative studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings, the diagnosis of TA was confirmed in june 2014. The allele HLA-B52 is the most frequently and strongly associated with TA in Japan and other Asian countries [8,9] and relates with worse clinical manifestations, higher rate of vascular complications and poor prognosis [10,11]. According to literature findings, our patients presented severe features suggesting a bad prognosis: the disease onset was underhand but the progression of thickening of the arterial walls was rapid and diffuse, leading to severe carotid occlusion and involving also the aortic bulb in case 2.…”
Section: Casementioning
confidence: 64%
“…The main reported association is with HLA-B5 and especially with its split B52 [8][9][10][11]. The allele B51 is also considered a possible gene of susceptibility but the evidence is weaker [12].…”
mentioning
confidence: 99%
“…Despite TAK primarily affecting young or middle-aged women, particularly from Asian countries, the disease has a worldwide distribution and has been reported in people of virtually all ages [ 11 ]. So far, the only genetic factor that shows a consistent association with TAK is the HLA allele, HLA-B*52, which has been confirmed in various cohorts and in several ethnicities [ 12 , 13 , 14 ]. Thus, it has been proposed that the increased prevalence of TAK in Asians may reflect the higher frequency of the HLA-B*52 in this population.…”
Section: Takayasu Arteritis: An Overviewmentioning
confidence: 98%